2018
DOI: 10.51985/jbumdc2018064
|View full text |Cite
|
Sign up to set email alerts
|

Incidence And Risk Factors Of Maternal And Fetal Outcomes Among Patients Of Placenta Previa With And Without Placenta Accreta

Abstract: Objective: The aim of the study was to evaluate maternal and fetal outcomes among patients of placenta previa (PP) with and without placenta accreta (PA). Methodology: All patients who underwent cesarean section for PP and PA were analyzed retrospectively at a tertiary care Combined Military Hospital Kharian, Pakistan, from February 2015 to March 2018. Maternal and neonatal data were obtained from medical records and the hospital database system. Results: PA was found in 37 patients from 111 patients of PP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
0
1
Order By: Relevance
“…They found the minority of the pregnant women had fetal growth restriction. While our study findings are in disagreement with previous studies by Khattak et al (2019). They revealed that fetal growth restriction was not seen.…”
Section: Discussioncontrasting
confidence: 99%
“…They found the minority of the pregnant women had fetal growth restriction. While our study findings are in disagreement with previous studies by Khattak et al (2019). They revealed that fetal growth restriction was not seen.…”
Section: Discussioncontrasting
confidence: 99%